Terör ve Şiddet Bağlamında Kullanılan Rivayetlerin Yorumlanması Üzerine - Nahide Bozkurt (Dini Araştırmalar, 2015)
After the events of September 11 th, the issue of terror, violonce and religion has once again come into intense discussion and debate. Especially after this event, “Islamic Terror and ’’Prophet Muhammad and Terror” has started to discuss again. In this context this question recurs again.”Was Prophet Muhammad “terrorist”? Some of authors claim that Prophet Muhammad was terrorist. In this conditions this subject needs to academic research. In order to understand Prophet Muhammad’s life truly and objectivly, we have to use historical methodolgy, My aim is to make a framework based upon main historical methodology and principals which are related Prophet Muhammad’s life